Praktik E-Money Pada Aplikasi Dana Perspektif Fatwa Dsn-Mui No. 116 Tahun 2017 - Ita Dwilestari (Bulletin of Indonesian Islamic Studies, 2024)
The use of the DANA application as a digital transaction tool further increases convenience in various types of payments. The implementation of financial technology in electronic money makes it easier for people to learn and use it in their daily lives. This research aims to understand the practice of e-money on the DANA application and analyze it in the perspective of DSN-MUI fatwa No. 116 of 2017. This research uses qualitative methods with primary and secondary data sources, as well as data collection methods through interviews and documentation. The results show that the practice of e-money on the DANA application involves the use of an active phone number to access the application, with the balance stored in an ESCROW account that can be used for payment transactions without additional fees. The e-money payment system on the DANA application is in accordance with the provisions of the DSN-MUI fatwa No. 116/DSN-MUI/IX/2017 concerning sharia electronic money. Transactions between users and issuers use a wadi'ah contract, which fulfills the terms and conditions of the contract. However, the contract between the merchant and the issuer does not fully fulfill the provisions of the wakalah bi al-ujrah contract, because the merchant does not receive ujrah or wages from the issuer.